2010
DOI: 10.1353/jhr.2010.0011
|View full text |Cite
|
Sign up to set email alerts
|

Back to Work: Expectations and Realizations of Work after Retirement

Abstract: This paper analyzes a puzzling aspect of retirement behavior known as “unretirement.” Nearly 50 percent of retirees follow a nontraditional retirement path that involves partial retirement or unretirement, and at least 26 percent of retirees later unretire. I explore two possible explanations: 1) unretirement transitions result from failures in planning or financial shocks; and 2) unretirement transitions are anticipated prior to retirement, reflecting a more complex retirement process. I show that unretiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
278
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(296 citation statements)
references
References 20 publications
12
278
0
6
Order By: Relevance
“…These data agree with the studies by Knoll (2011) andMaestas (2010), which highlighted that perception of low financial status is not the main reason for return to work during retirement. Knoll also found that people with better health conditions and socioeconomic level tend to work for a longer time than those who are less healthy and have poor financial conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data agree with the studies by Knoll (2011) andMaestas (2010), which highlighted that perception of low financial status is not the main reason for return to work during retirement. Knoll also found that people with better health conditions and socioeconomic level tend to work for a longer time than those who are less healthy and have poor financial conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Our conclusions agree with data in the literature and affirm that reasons for continuing to work in retirement are related to psychosocial factors (Khoury et al, 2010;Maestas, 2010;Wöhrmann et al, 2014). Our study sought to assess parallels with satisfaction with life and showed the factors of higher impact with satisfaction with life were the professional, relational, and intrinsic perception reasons to return to work, which caused a break in retirement.…”
Section: Discussionsupporting
confidence: 89%
“…Instead of following the traditional retirement pattern (i.e., leaving a full-time career job for full retirement without reentry), nearly 50 % of older Americans are choosing to gradually reduce their workforce commitment by taking a bridge job (i.e., taking a new job after retirement from a career job) or go through phased retirement (i.e., continuing to work part-time with the same employer to supplement retirement benefits); many of them experience multiple transitions among employment, non-work, and retirement status (Cahill et al 2006;Maestas 2010;Purcell 2005). For many older persons, work trajectories are characterized by a sequence of transitions, including full-time employment, part-time employment, unemployment, and labor force nonparticipation.…”
Section: Recent Retirement Trends and Patternsmentioning
confidence: 99%
“…Bridge jobs are becoming more prevalent among members of more recent cohorts (Giandrea et al 2009). It was estimated between 48 % and 60 % of the sample subjects experienced labor force reentry within six years after retirement (Maestas 2010). Thus the existing evidence shows considerable variability in the pathways to retirement.…”
Section: Recent Retirement Trends and Patternsmentioning
confidence: 99%
See 1 more Smart Citation